1979
DOI: 10.1172/jci109583
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Papillary Micropuncture Examination of Chloride Transport in Segments of the Rat Kidney during Inhibition of Prostaglandin Production

Abstract: A B S T R A C T Prostaglandins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 18 publications
(27 reference statements)
2
24
0
Order By: Relevance
“…The left femoral artery was cannulated to monitor blood pressure and for collection of arterial blood samples. The left kidney was exposed by a flank incision and prepared for micropuncture of the renal cortex as previously described (8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The left femoral artery was cannulated to monitor blood pressure and for collection of arterial blood samples. The left kidney was exposed by a flank incision and prepared for micropuncture of the renal cortex as previously described (8)(9)(10).…”
Section: Methodsmentioning
confidence: 99%
“…This was accomplished by collecting paired samples of tubule fluid from an early and late segment ofthe same PCT. Tubule fluid samples were collected for timed intervals (2.5-6 min) using sharpened 8-10-,gm OD glass pipettes as previously described (8,9). In each tubule, the late proximal segment was punctured before the early proximal segment to prevent leakage of tubule fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been suggested that the site(s) for this process might include juxtamedullary proximal tubules, the loops of Henle, or more distal segments (6) (12,13). Transit times > 13 s or a mean arterial blood pressure < 100 mm Hg were cause for rejection at this point.…”
Section: Introductionmentioning
confidence: 92%
“…Acid-base status of the rat was monitored and carefully maintained exactly as previously described (14,15). Micropuncture of the desired cortical or papillary nephron segment was accomplished with sharpened micropipettes containing Sudan-colored mineral oil exactly as previously described in detail (12,13). Descending or ascending vasa recta samples were collected in some of the groups noted below by the technique described by Lacy (17) immediately after collection as previously described (14).…”
Section: Introductionmentioning
confidence: 99%
“…In rat micropuncture experiments, Higashihara et al (41) have demonstrated a decrease in NaCl delivery to distal tubule sites and an increase in papillary NaCl PGE2 Effects on Cl-Absorption in mTALH content following prostaglandin synthesis inhibition; they concluded that prostaglandins might inhibit NaCl transport in the TALH. Complementary studies conducted by Kaukker (42), using micropuncture techniques, and by Stokes (43), using the isolated, perfused rabbit mTALH, have also been consistent with the notion that PGE2 inhibits NaCl absorption by the TALH.…”
mentioning
confidence: 98%